Association of Common Variations on Chromosome 4q25 and Left Atrial Volume in Patients with Atrial Fibrillation - Yuliya Mints; Hirad Yarmohammadi; Irfan M. Khurram; Hana Hoyt; Rozann Hansford; Stefan L. Zimmerman; Steven J. Steinberg; Daniel P. Judge; Gordon F. Tomaselli; Hugh Calkins; Vadim Zipunnikov; Saman Nazarian (Clinical Medicine Insights: Cardiology, 2015)
Aims Recent studies have shown that several genetic variants near the PITX2 locus on chromosome 4q25 are associated with atrial fibrillation (AF). However, the mechanism that mediates this association remains unclear. Basic murine studies suggest that reduced PITX2 expression is associated with left atrial dilatation. We sought to examine the association between single nucleotide polymorphisms (SNPs) near PITX2 and left atrial size in patients with AF. Methods We prospectively enrolled 96 consecutive patients (mean age 60 ± 10 years, 72% male) with drug-resistant AF (57% paroxysmal, 38% persistent, and 5% long-standing persistent) who underwent catheter ablation. Following DNA extraction from blood obtained pre-operatively, SNPs rs10033464 and rs2200733 were genotyped using the Sequenom MassARRAY. Left atrial volume (LAV) was determined using three-dimensional imaging (CT or MRI prior to first ablation) and by investigators blinded to genotype results. Results The minor allele frequencies at SNPs rs10033464 and rs2200733 were 0.14 and 0.25, respectively. Using multivariable linear regression, homozygosity for the minor allele at rs10033464 (recessive model) was independently associated with larger LAV ( P = 0.002) after adjustment for age, gender, BMI, height, type, and duration of AF, left ventricular ejection fraction, history of hypertension, valve disease, and antiarrhythmic drug use. The strength of the association was reconfirmed in a bootstrap study with 1000 resamplings. In contrast, no association was found between rs2200733 variant alleles and LAV. Conclusion SNP rs10033464 near the PITX2 locus on 4q25 is associated with LAV. Left atrial dilatation may mediate the association of common variants at 4q25 with AF.